Management of the teamwork activity of teachers in the early childhood education institution - Lilia CEBANU; Alina IVAN (Acta et Commentationes, Sciences of Education, 2023)
The management of the teamwork activity of teachers in the early childhood education institution is an important and relevant process that has a significant impact on the quality of education provided to preschoolers. This process involves defining clear objectives and roles, open and effective communication, developing leadership skills, continuous training, evaluating and monitoring performance. By implementing these measures, the quality of the education provided can be improved, creating a strong and efficient team that contributes to the success of the whole process.